DEVELOPMENT OF COMPETITION AND ITS PROTECTION IN KOSOVO - Gani Asllani (European Scientific Journal, ESJ, 2012)
This paper investigates development and protection of competition in Kosovo, legislative aspect of its adjustment, the most sensitive sectors where the competitions is damaged and finally are presented the measures on improvement based on the EU practices. To the economies in transition as Kosovo is, three types of anti competition practices that are object of the law on competition draw particular importance. This anti-competition practices are: prohibited agreements-cartels, mergers of enterprises and misuse of dominant position of the enterprises that have relevant influence on the market. Competition damage in those economies may be done in two directions: from the side of enterprises that make agreements, mergers, abuse with the dominant position and in these activities they damage the market structure, at the other hand the state by creating legal monopoles, giving the exclusive rights and other activities that may create discrimination as well as from the non-transparence of the politics of state aid.